Exploring the effect of formulation parameters on the particle size of carboxymethyl chitosan nanoparticles prepared via reverse micellar crosslinking. (3rd April 2017) - Sheikholeslami, Zeinab Sadat; Salimi-Kenari, Hamed; Imani, Mohammad; Atai, Mohammad; Nodehi, Azizollah
Abstract: Carboxymethyl chitosan (CMCh), as a non-toxic, biocompatible and biodegradable semi-synthetic biopolymer with mucoadhesive properties, is widely investigated for targeting drug or gene delivery applications. Here, fabrication of CMCh nanoparticles will be reported using a reverse (w/o) micellar system to provide particles with tuneable mean sizes. Reverse microemulsions were prepared by dispersing aqueous solution of CMCh in n -hexane using sodium-bis(ethylhexyl)-sulfosuccinate (AOT) and glutaraldehyde (GA) as an emulsifier and a crosslinking agent, respectively. The obtained particles were perfectly spherical in the nanometric size range (40–140 nm) with a narrow size distribution according to the FE-SEM images. To determine the effective parameters on the mean nanosphere size, CMCh, AOT and GA concentrations were varied according to a full-factorial, three-level design-of-experiments. After evaluating the results, it was found that AOT and CMCh concentrations had a significant effect on the mean nanosphere size while GA concentration surprisingly showed non-significant, minor effects on the same response.